TOXOPLASMOSIS EN ALPACAS DE LA SIERRA ALTOANDINA - Suárez A., Francisco (2004)
The objective of this study was to determine the prevalence of toxoplasmosis (Toxoplasma gondii) in an alpaca farm in the southern part of Peru. Blood samples of 278 alpacas (68 male and 210 females) of different ages were collected and analyzed using the indirect immunofluorescense test. The prevalence was 34.5% (CI0.95 = 28.9 ? p ? 40.1%). The prevalence was significantly affected (p<0.05) by sex (males: 3.0; females: 44.8%) and age (?3 years = 16.7; > 3 years = 40.8).